Criminal law policy in the framework of children contact with the law - Purwati, Ani (Technium Social Sciences Journal, 2022)
The dynamics of criminal law in Indonesia are currently experiencing complexity, because there are still children who commit legal acts such as violence, destruction, or child delinquency that results in murder. However, this is triggered by the unstable psychological and mental state of the child, the surrounding environment or way of life that grows and develops in people’s lives as well as civility in communicating and socializing with people’s lives. Distortion of children who are in conflict with the law when they have to prioritize attitudes, morals and skills, so there needs to be a criminal law policy in order to prioritize human values and skills (soft skills) when they are processed in correctional institutions. This research is focused on fostering skills and creativity for children who are in conflict with the law at the correctional institution at the UPT for Social Protection and Rehabilitation Marsudi Putra Surabaya. This study uses a sociological juridical approach by emphasizing research that aims to obtain legal knowledge empirically by going directly to the object. If you look at the results and analysis of the findings, that children who are in conflict with the law have felt mentally and psychologically destroyed, so they need to be triggered by skill activities such as making crafts and technology in the penitentiary at the UPT for Social Protection and Rehabilitation Marsudi Putra Surabaya. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA) mandates the formation of the Child Special Guidance Institution (LPKA). This is an improvement step towards fostering children who are in conflict with the law, because before LPKA was formed, it was still found that child prisoners were placed in one penitentiary joining adult inmates. At the Social Protection and Rehabilitation UPT Marsudi Putra Surabaya, the reality is that LPKA has been formed by carrying out activities that support productivity and skills. What happened to the Directorate General of Corrections at the Ministry of Law and Human Rights to: first, prepare LPKA officers from various disciplines, such as psychologists, crimonologists, criminal experts, and sociologists; second, increasing training related to fostering children in conflict with the law for LPKA officers; and third, increasing cooperation with relevant agencies in providing guidance for children in conflict with the law. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA) aims to create a court that truly guarantees the protection of the best interests of children in conflict with the law. The SPPA Law is a substitute for Law No. 3 of 1997 concerning Juvenile Courts (Children Court Law), because the Juvenile Court Law is considered no longer in accordance with legal needs in society and has not comprehensively provided special protection to children in conflict with the law.